Development of Mn-Si-MEL as a bi-functional adsorption-catalytic oxidation material for VOCs elimination - Yu, Qingjun; Feng, Yongchao; Wei, Jinghui; Tang, Xiaolong; Yi, Honghong (Chinese chemical letters, 2022)
Mn-Si-MEL zeolite was developed as a bi-functional adsorption-catalytic oxidation material for volatile organic compounds (VOCs) elimination due to its good hydrophobicity & good organophileproperty brought by the substitution of Mn for Al in zeolite and the superior catalytic oxidation property endowed by the existence of Mn species. Various Mn-Si-MEL samples were obtained by introducing Mn to MEL crystallization system via different ways. It was found the incorporated Mn ways have a significant effect on the behavior of Mn being involved in the crystallization of MEL and finally influenced the distribution of Mn in zeolite as well the physicochemical properties of product zeolite. The seeding method (Mn-S2(Seed)) is favorable for the good incorporation and uniform distribution of Mn in zeolite while both recrystallization method (Mn-S2(RC)) and direct synthesis method (Mn-S2(DH)) are favorable for obtaining more reducible Mn species and surface adsorbed oxygen species. The Mn amount incorporated into zeolite follows Mn-S2(RC) (1.96 wt%) > Mn-S2(Seed) (1.07 wt%) ≈ Mn-S2(DH) (0.97 wt%), the adsorption capacity of various samples follows Mn-S2(Seed) (83.3 μmol/g) ≈ Mn-S2(RC) (82.1 μmol/g) > Mn-S2(DH) (76.1 μmol/g), while the catalytic oxidation ability of three samples follows Mn-S2(RC) ≈ Mn-S2(DH) > Mn-S2(Seed). Furthermore, Mn-S2(RC) which exhibits both superior adsorption capacity and catalytic oxidation ability shows good hydrophobicity and superior recyclability, demonstrating its great potential to be applied in the VOCs elimination by an enrichment-degradation route. Mn-Si-MEL zeolite was developed as a bi-functional adsorption-catalytic oxidation material for VOCs elimination due to its good hydrophobicity & good organophileproperty brought by the substitution of Mn for Al in zeolite and the superior catalytic oxidation property endowed by the existence of Mn species. [Display omitted]